Canadian stroke best practice consensus statement: Secondary stroke prevention during pregnancy. Issue 4 (June 2018) - Swartz, Richard H; Ladhani, Noor Niyar N; Foley, Norine; Nerenberg, Kara; Bal, Simerpreet; Barrett, Jon; Bushnell, Cheryl; Chan, Wee-Shian; Chari, Radha; Dowlatshahi, Dariush; Amrani, Meryem El; Gandhi, Shital; et al.
The Canadian Stroke Best Practice Consensus Statement: Secondary Stroke Prevention during Pregnancy, is the first of a two-part series devoted to stroke in pregnancy. This document focuses on unique aspects of secondary stroke prevention in a woman with a prior history of stroke or transient ischemic attack who is, or is planning to become, pregnant. Although stroke is relatively rare in this cohort, several aspects of pregnancy can increase stroke risk during or immediately after pregnancy. The rationale for the development of this consensus statement is based on the premise that stroke in this group requires a specifically-tailored management approach. No other broad-based, stroke-specific guidelines or consensus statements exist currently. Underpinning the development of this document was the concept that maternal health is vital for fetal wellbeing; therefore, management decisions should be based on the confluence of two clinical considerations: (a) decisions that would be made if the patient was not pregnant and (b) decisions that would be made if the patient had not had a stroke. While empirical research in this area is limited, this consensus document is based on the best available literature and guided by expert consensus. Issues addressed in this document include general management considerations for secondary stroke prevention, the use of antithrombotics, blood pressure management, lipid management, diabetes care, and management for specific ischemic stroke etiologies in pregnancy. The focus is on maternal and fetal health while minimizing risks of a recurrent stroke, through counseling, monitoring, and the safety of select pharmacotherapy. These statements are appropriate for health care professionals across all disciplines.